Edukasi pencegahan hipertensi dan pengetahuan minum obat di lingkungan Pemuda Muhammadiyah Ngaglik - Astyamalia, Suzan; Kemila, Mira (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
Hypertension is included in top ten diseases in Sleman Regency 2023 for all age groups. Men have a risk 3 times greater than women. There is a significant relationship between the level of knowledge and adherence to taking medication in hypertensive patients. Therefore, it is necessary to provide services in the form of education regarding the prevention of hypertension and knowledge regarding adherence to taking antihypertensive medication among young people in Sleman. The service was carried out in Sleman Regency with 20 Muhammadiyah youth from Sleman Regency as participants. The service instrument used is a questionnaire. The data was analyzed by classifying the level of education and assessing the percentage of knowledge level of the respondents' answers, which was 50% good, 40% sufficient and 10% less. The results concluded that education had a good impact on the level of knowledge for some respondents.